Hubungan Pelaksanaan Manajemen Laktasi oleh Petugas Kesehatan terhadap ASI Eksklusif pada Ibu Menyusui - Achmad Djamil; Nur Sefa Arief Hermawan; N. Setiarini (Politeknik Kesehatan Tanjung Karang, 2018)
Nationally, exclusive breastfeeding coverage for infants aged less than six months was 55.7%. Lampung province data for exclusive breastfeeding coverage in infants aged 0-6 months was still lower than the national age of 54.9% and has not reached the target of Renstra 2015-2019 was 60% (Ministry of Health RI, 2015). The purpose of this research was to know the relation of lactation management implementation by health officer to exclusive breastfeeding in breastfeeding mothers in Krui Pesisir West District of Lampung in 2017. This study was a quantitative research type, with the cross-sectional approach. The population was a lactating mother with a 0-6-month-old baby in region work Puskesmas Krui Pesisir West District, as many as 60 people. Data collection were using observation sheets. Data analysis was by bivariate using chi-square. The results of the study showed there was a relationship of lactation management implementation by health workers to exclusive breastfeeding in breastfeeding mothers at Krui Pesisir West District 2017 (p-value:0,031 and Odd Ratio: 5,37). The suggestion needs to improve education again as well as motivation on the importance of exclusive breastfeeding for breastfeeding mothers and to be more proactive in evaluating the implementation of exclusive breastfeeding coverage during breastfeeding mothers, with the aim of increasing the coverage of exclusive breastfeeding in infants aged 0-6 months.